X-linked recessive myotubular myopathy with MTM1 mutations - Han, Young-Mi (The Korean Pediatric Society, 2013)
X-linked recessive myotubular myopathy (XLMTM) is a severe congenital muscle disorder caused by mutations in the MTM1 gene and characterized by severe hypotonia and generalized muscle weakness in affected males. It is generally a fatal disorder during the neonatal period and early infancy. The diagnosis is based on typical histopathological findings on muscle biopsy, combined with suggestive clinical features. We experienced a case of a newborn who required intubation and ventilator care because of profound hypotonia and respiratory difficulty. The preliminary diagnosis at the time of request for retrieval was hypoxic ischemic encephalopathy, but the infant was clinically reevaluated for generalized weakness and muscle atrophy. Muscle biopsies showed variability in fiber size and centrally located nuclei in nearly all the fibers. We detected an MTM1 gene mutation of c.1261-1C>A in the intron 10 region, and diagnosed the neonate with myotubular myopathy. The same mutation was detected in his mother.